Does a 4-week training period with hand paddles affect front-crawl swimming performance? - Barbosa, A. C.; Ferreira, T. H. N.; Leis, L. V.; Gourgoulis, V.; Barroso, R. (Journal of Sports Sciences, 2020)
This study investigated the effects of a 4-week training with hand paddles (HPD) on front-crawl swimming performance (SP), clean swimming speed (SPEED), stroke rate (SR), stroke length (SL) and tethered force (TF). Twenty swimmers (10 men and 10 women) were paired according to performance and gender, and were randomly assigned to control (CON, 22.4 ± 2.3 years) or HPD (21.8 ± 1.9 years) groups. During 4 weeks both groups performed the same training, except for a sprint training set (3 times/week, 10 × 10 strokes all-out, 1-min rest) completed with (HPD = 320 cm2) and without (CON) paddles. Afterwards, both groups performed the same training over a 2-week taper period. SP, SPEED, SR, SL and TF were assessed before (PRE) and after the 4-week period (POST), after the first (T1) and second taper weeks (T2). Swimmers rated their perceived exertion for the sprint training set (RPETS) and the training session for determining internal training load (ITL). SP, SPEED, SR, SL and TF did not change from PRE to POST, T1 and T2. ITL and RPETS were not different between groups. Training 4 weeks with HPD does not affect swimming performance, so the use of HPD remains unsupported in such period.